How to Reduce Clogging Problems in Fertigation - Guodong Liu; Gene McAvoy (EDIS, 2012)
Fertigation is the process of applying fertilizers through an irrigation system by injecting them into the water. Because of its effectiveness and efficiency, fertigation is widely used in vegetable and fruit production. However, clogging of lines and emitters may become a problem. This 7-page fact sheet provides practical suggestions for better fertigation management so growers can reduce clogging problems. Written by Guodong Liu and Gene McAvoy, and published by the UF Department of Horticultural Sciences, June 2012.